A Lyapunov function and global properties for SIR and SEIR epidemiological models with nonlinear incidence - Korobeinikov, A; Maini, P (2004)
Explicit Lyapunov functions for SIR and SEIR compartmental epidemic models with nonlinear incidence of the form $β I_p S_q$ for the case p<1 are constructed. Global stability of the models is thereby established.